2021
DOI: 10.3390/cells10071595
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive Properties and Powerful Neuromodulation of Nav1.6 Sodium Channels Regulates Neuronal Excitability

Abstract: Voltage-gated sodium channels (Navs) are critical determinants of cellular excitability. These ion channels exist as large heteromultimeric structures and their activity is tightly controlled. In neurons, the isoform Nav1.6 is highly enriched at the axon initial segment and nodes, making it critical for the initiation and propagation of neuronal impulses. Changes in Nav1.6 expression and function profoundly impact the input-output properties of neurons in normal and pathological conditions. While mutations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 230 publications
(385 reference statements)
1
25
0
Order By: Relevance
“…As described by Milescu et al [55], a depolarizing pre-pulse step was used to inactivate Na v channels distant from the recording electrode, and a second step was applied shortly afterward to record the Na v channels close to the recording pipette (Figure 2A), similar to our previous publication [56]. Importantly, hippocampal CA1 pyramidal neurons represent a promising cellular target to be affected by changes in Akt signaling, as these cells abundantly express Na v 1.6 channels where they contribute to somatic I Na and intrinsic excitability, Na v 1.6 channels are abundantly expressed in hippocampal CA1 pyramidal neurons, where they contribute to somatic I Na and intrinsic excitability [57][58][59][60]. 2.…”
Section: Effects Of Pharmacological Inhibition Of Akt On Na V 16-enco...supporting
confidence: 82%
“…As described by Milescu et al [55], a depolarizing pre-pulse step was used to inactivate Na v channels distant from the recording electrode, and a second step was applied shortly afterward to record the Na v channels close to the recording pipette (Figure 2A), similar to our previous publication [56]. Importantly, hippocampal CA1 pyramidal neurons represent a promising cellular target to be affected by changes in Akt signaling, as these cells abundantly express Na v 1.6 channels where they contribute to somatic I Na and intrinsic excitability, Na v 1.6 channels are abundantly expressed in hippocampal CA1 pyramidal neurons, where they contribute to somatic I Na and intrinsic excitability [57][58][59][60]. 2.…”
Section: Effects Of Pharmacological Inhibition Of Akt On Na V 16-enco...supporting
confidence: 82%
“…Pyrethroids (e.g., permethrin and cypermethrin), known to activate I Na , have also been reported to disrupt NOX activity in brain tissue (striatum) [ 49 ]. Therefore, through ionic mechanisms shown herein, pyrethroids or other structurally similar compounds are able to adjust the functional activities of varying types of neuroendocrine or endocrine cells, or heart cells, if similar in vivo results exist [ 6 , 7 , 11 , 12 , 13 , 50 ]. To this end, the overall findings from our study highlight an important alternative aspect that has to be taken into account, inasmuch as there is the beneficial or ameliorating effect of aPO in various pathologic disorders, such as inflammatory or neurodegenerative diseases, and heart failure [ 1 , 3 , 6 , 7 , 9 , 10 , 11 , 12 , 13 , 16 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we have found that the I Na mediated by the Na V 1.6 channel not only are crucial players in neuronal hyperexcitability ( Patel et al, 2016 ; Wang et al, 2016 ; Ciccone et al, 2019 ; Zybura et al, 2021 ), but also modulate [Ca 2+ ] i by inducing the activation of the NCX reverse activity thus providing a Ca 2+ source from the extracellular space to refill the ER Ca 2+ stores. This evidence sheds new light on the Na V 1.6 upregulation in AD neurons and suggests that its downstream effects may also depend on channel sub-cellular localization as well as on Na V 1.6 interacting proteins.…”
Section: Discussionmentioning
confidence: 59%